Prevalence of use of medicinal plants and its relationship with health literacy and attitude among pregnant women - Nazanin Ghasemi; Shabnam Omidvar; Sana Nazmi (Mashhad University of Medical Sciences, 2023)
Introduction: Women are the main users of medicinal plants and they usually continue using them during pregnancy without considering the potential maternal and fetal risks. The present study was performed with aim to determine the frequency of consumption of medicinal plants and its relationship with health literacy and attitude of pregnant women towards medicinal plants. Methods: This descriptive-analytical and retrospective study was conducted in 2022 on 322 pregnant women who visited the hospitals in the west of Mazandaran for delivery. Data collection tools was questionnaire that the first part included the demographic characteristics and the pattern of medicinal plant consumption, the second part was the attitude toward the consumption of medicinal plants, and the third part was the health literacy. Data were analyzed by SPSS software (version 25) and Independent t and Chi-square tests. P<0.05 was considered statistically significant. Results: Among 322 pregnant women participated in this study, 134 (41.6%) consumed medicinal plants during pregnancy. The most common reason for consumption was digestive problems. Mint and borage were the most commonly used herbs. The first and third trimesters of pregnancy were the most common times of consuming herbs (65.5%). No relationship was found between the frequency of consumption with demographic characteristics and health literacy, but a significant relationship was found between frequency of consumption and attitude towards medicinal plants (P<0.001). Conclusion: Considering the relationship between prevalence of medicinal plant consumption and attitude towards medicinal plants, and lack of the relationship with health literacy, it is necessary to take a fundamental action to improve the attitude and raise the awareness of pregnant women regarding the use of medicinal plants.